Analysis of Sharia Bank Financial Reports on Industrial Accounting Instruments - Rosana, Jackie; Jessica, Jessica; Pangestu, Krisnawati Yeni; Shelsy, Shelsy; Simdy, Vivian; Dewi, Sari (Jurnal Ekonomi Balance, 2024)
This research aims to analyze accounting instruments in the financial reports of PT Bank Syariah Indonesia Tbk (BSI) and classify the types of instruments based on the social requirements pyramid. The research method uses quantitative analysis by reviewing BSI's financial reports for the 2020-2022 period. Data is analyzed to identify murabahah, istishna, ijarah receivables, as well as mudharabah and musyarakah financing. The research results show that murabahah, istishna and ijarah receivables experience significant changes from year to year. In 2020, Murabahah receivables amounting to 86,564,664 million rupiah, increased to 98,333,857 million rupiah in 2021, and 120,700,195 million rupiah in 2022. Istishna receivables showed a decrease from 607 million rupiah in 2020 to 131 million rupiah in 2022. receivables Ijarah also experienced fluctuations with a total of 23,917 million rupiah in 2020, decreasing to 1,653 million rupiah in 2022. Mudharabah and musyarakah financing also showed a changing trend, with mudharabah financing falling from 2,598,787 million rupiah in 2020 to 1,001,957 million rupiah in 2022, while musyarakah financing increased from 50,896,175 million rupiah in 2020 to 66,450,946 million rupiah in 2022. The conclusion of this research states that BSI has fulfilled its economic, legal and ethical responsibilities in accordance with the pyramid of social requirements. The classification of financial instruments shows that mudharabah and musyarakah are included in the sharia-based category, while ijarah, istishna, and murabahah are included in the sharia compliance category. These findings show that BSI operates in accordance with sharia financial principles, making a positive contribution to national economic development and community welfare